1985
DOI: 10.1017/s003329170002105x
|View full text |Cite
|
Sign up to set email alerts
|

The List of Threatening Experiences: a subset of 12 life event categories with considerable long-term contextual threat

Abstract: SYNOPSIS In a survey of a random sample of the general population recent life events, collected and rated for long-term contextual threat according to the methods of Brown & Harris (1978), were also recorded wftere possible on an inventory of life event categories (Tennant & Andrews, 1977). Of the 82.5 % of all events collected which were covered by the inventory, 12of the 67 event categories accounted for 77% of life events with an aetiologicaly significant rating of marked or moderate long-term threat. Where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
729
1
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 989 publications
(742 citation statements)
references
References 15 publications
4
729
1
8
Order By: Relevance
“…The List of Threatening Experiences Questionnaire (LTE-Q) 29 was used to measure the occurrence of SLEs. The LTE-Q is a 12-item, self-report checklist, which was previously adapted to include childbirth and the subjective severity rating of each item.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The List of Threatening Experiences Questionnaire (LTE-Q) 29 was used to measure the occurrence of SLEs. The LTE-Q is a 12-item, self-report checklist, which was previously adapted to include childbirth and the subjective severity rating of each item.…”
Section: Methodsmentioning
confidence: 99%
“…30 Although the list of threatening experiences includes just 12 items, previous analyses have shown that the measure successfully captures 82.5% of the life events covered in the longer more extensive, and widely accepted, Life Events and Difficulties Schedule. 29 Participants completed the LTE-Q for events that they had experienced in the 6 months before commencing treatment. In all, 674 participants completed the checklist at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…The List of Threatening Experiences (LTE-Q) (Brugha, Bebbington, Tennant, & Hurry, 1985;Brugha & Cragg, 1990;Stewart et al, 2002) has been frequently used to quantify the number of negative or stressful life events (such as bereavement). If adequately measured, patterns of health status and number of adversities should distinguish: i) mentally healthy people experiencing few negative life events (externally protected), ii) people with poorer mental health and many negative life events (vulnerable and non-resilient), iii) people with good mental health despite negative life events (resilient).…”
Section: Measures Of Mental Resiliencementioning
confidence: 99%
“…Assessment of adverse event experience in adulthood was restricted to those incidents considered most likely to be remembered reliably over an extended period. Event selection was based upon those developed for the questionnaire version of the List of Threatening Experiences (LTE-Q) [19]. A total of 16 specific adverse events, and a further undefined event of personal significance, were included in the questionnaire with up to two most recent events recorded and dated.…”
Section: Social Adversity Assessmentmentioning
confidence: 99%